Aikido, un arte marcial (acceso a otro modo de ser) - José Santos Nalda Albiac (Universidad de León, 2012)
André Protin. Barcelona: Ibis, 1998 (3ª ed.). 326 páginas. 21,50x15 cm. I.S.B.N.: 84-86512-34-4.